PENGARUH BIAYA PROMOSI TERHADAP TINGKAT VOLUME PENJUALAN PADA PT. ISTANA DELI KEJAYAAN (IDK2) - Rahmania Nasution; Alistraja Dison Silalahi; Ova Novi Irama (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2020)
The purpose of this study is to determine whether promotional costs affect the sales volume level at PT. Istana Deli Kejayaan (IDK2). This study uses quantitative data analysis. The population used is a report on promotion costs and sales volume in 2016 to 2018. The research sample is a report on promotion costs and monthly sales volume. The number of samples is 12 months x 3 years = 36 months. The research was conducted at PT. Istana Deli Kejayaan (IDK2) which is located at Jl. Sei Batang Hari No.22 Babura Sunggal. The time of the research was conducted in January 2019 until July 2019. The results of this study concluded that promotion costs had a positive and significant effect on the level of sales volume at PT. Istana Deli Kejayaan (IDK2). The effect of promotional costs on the level of sales volume is 31,0%, while the remaining 69.0% is influenced by other variables not discussed in this study.